Ultrasound biomicroscopy and secondary epithelial downgrowth cysts of anterior chamber - Adan,Consuelo B. D. (1998)
SUMMARY Purpose: To determine clinical and ultrasound correlation of secondary implantation iris and anterior chamber cysts, reported after trauma or intraocular surgeries. Patients and Methods: Retrospective study of ultrasonographic biomicroscopy examinations (UBM Model 840 - Humphrey Instruments, USA, equipped with a 50 MHz transducer, utilizing immersion technique), performed from August 1994 to July 1997 at the Ocular Ultrasound Section, UNIFESP-EPM. Results: In a total of 1,669 UBM examinations, 8 cases of secondary epithelial implantation cysts were found, among them 3 after trauma (2 presenting as a white lesion, whose anatomopathological sections showed concentric lamellae of keratin; another with penetrating ocular trauma presenting a lesion with hypodense content) and 5 cases after intraocular surgery (post-extracapsular extraction, 3 cases; post-penetrating corneal graft, 2 cases). On UBM, secondary implantation cysts were identified as unilateral lesions, with hypodense content (with particles in suspension, or epithelial ceils) or disposed in concentric hyperreflective lamellae (keratin). In all the cases of hypodense content (6), delamination of iris stroma was observed, an information unavailable by other methods. Utilizing UBM examination, postoperative evaluation was performed in 2 cases (1 submitted to surgical removal, another to laser cystotomy) or serial examination if clinical observation was decided. Conclusion: UBM examination was able to differentiate the type of anterior chamber epithelialization (cystic, solid and sheet-like forms), to detect associated lesions indicating the most appropriate treatment, its results when performed, and its follow-up.